(untitled) (Annals of the University of Bucharest. Philosophy Series, 2025)
The issue surrounding the Name Controversy on Mount Athos in early 20th century provoked a long and systematic response from Father Sergius Bulgakov in defense of the hesychastic prayer in the Name of Jesus. Two remarkable aspects of the response deserve attention. The first is the self-conscious identification of his defense with that of St Gregory Palamas’ in the 14th century, also involving the prayer life of the hesychasts and the Jesus Prayer. The essay argues for the Bulgakov’s working within the framework of Palamite doctrine, wishing to “further” it. The second has to do with this furtherance via a creative reworking modern German philosophy within the perspective of the dogma of consubstantiality in order to establish the ontological character of the Name and especially the one invoking Jesus.